Impact of Seismic Design on Embodied Carbon in Steel Buildings: A Structural Element-based Assessment - Keintjem, Militia; Suwondo, Riza; Suangga, Made (Engineering, Technology & Applied Science Research, 2025)
The building and construction sector is a major contributor to global carbon emissions, with Embodied Carbon (EC) from material production, transportation, and construction gaining increasing attention. Although seismic design enhances structural safety, it also leads to a higher material consumption, thereby increasing the EC footprint of the buildings. This study examines the impact of seismic design on EC in steel buildings, focusing on columns, beams, and floors. A two-story steel-framed building was analyzed under low, moderate, and high seismic intensities. The EC assessment followed BS EN 15978, considering cradle-to-gate emissions (stages A1–A3) using industry-standard Inventory of Carbon and Energy (ICE) database values. Structural modeling was conducted using ETABS to determine the material demands. The results showed that the total EC increased by approximately 51% from non-seismic to high seismic conditions. Columns and beams exhibited the highest proportional increase owing to the larger cross-sectional sizes required for seismic stability, while concrete slabs contributed the most absolute emissions. Steel components, however, exhibited the greatest relative rise in carbon intensity. To reduce the EC in seismic design, structural optimization methods, high-strength steel utilization, and material reuse strategies should be explored. This study provides a scientific foundation for integrating sustainability into seismic regulations, thus contributing to low-carbon structural solutions for earthquake-prone regions.